Reinvesting in the Lives of Youth: A Targeted Approach to Reducing Recidivism - Schweitzer, Myrinda (Criminal justice policy review, 2017)
Justice reinvestment strategies have been proposed to allow financial resources originally allocated for imprisonment to be reinvested into community-based alternatives. According to this perspective, the government has the responsibility to fund strategies that reduce crime, and previous studies have questioned the effectiveness of prison as one solution. Furthermore, empirical support for community-based alternatives underscores the importance of delivering interventions in offenders’ natural environments. This study explores one state’s attempt to fund strategies that reduce crime and delinquency. Through the Targeted Reasoned and Equitable Community and Local Alternatives to the Incarceration of Minors (RECLAIM) initiative, the State of Ohio attempted to reduce the risk of recidivism by serving more youth locally, instead of in secure facilities in the six most populous counties throughout the state. Specifically, the findings suggest that the Targeted RECLAIM initiative was successful in reducing the risk of recidivism of participating youth.